Upaya Meningkatkan Kesadaran Remaja Putri Dalam Melakukan Pemeriksaan Payudara Sendiri (SADARI) - Umi Narsih; Homsiatur Rohmatin; agustina widayati (CV. Multi Kreasi Media, 2023)
Breast cancer is a type of cancer that has the highest incidence rate in Indonesia. The incidence of breast cancer increases with age. being young is not a guarantee of being safe from breast cancer. The high incidence of breast cancer results in not a few breast cancer sufferers which lead to death. One of the efforts for early detection of breast cancer is to carry out breast self-examination (SADARI), which is a simple, inexpensive, non-invasive, and harmless early detection program. situation in increasing awareness of young women in carrying out breast self-examination (SADARI). The method used is in collaboration with the Darul Ulum Islamic Boarding School by providing education, training and support regarding SADARI. An indicator of the success of this activity is encouraging young women to take active and responsible action in efforts to prevent breast cancer. It is hoped that the activities that will be carried out can run smoothly so that good benefits will be obtained starting from increasing knowledge about SADARI and young women being able to do SADARI. At first the young women felt embarrassed when they were asked to practice. SADARI, however, after being motivated and exemplified directly by the community service team using existing media (phantom), young women were able to overcome their shyness. This activity shows encouraging results. All young women understand and understand and are able to demonstrate the correct way of SADARI. Furthermore, young women apply SADARI in their daily lives. Keywords: awareness, young women, breast self-examination, realize